PENGARUH PENDAPATAN ASLI DAERAH, SELISIH LEBIH PERHITUNGAN ANGGARAN DAN FLYPAPER EFFECT PADA PERILAKU OPORTUNISTIK PENYUSUN ANGGARAN - Sutha Megasari, Ida Ayu Gede (Buletin Studi Ekonomi; VOL.20.NO.2.AGUSTUS 2015 (PP 83-176), 2016)
The Effect of Local Revenue, Surplus of Financing Budget, and Flypaper Effect on Opportunistic Behavior of Regency/City Budget Compiler. Opportunistic behavior is a behavior which trying to achieve the desire in every way even that is illegal. This research aims to examine PAD, SiLPA and flypaper effect on the OPA. This research used the secondary data. The amount of the populations were 9 Regency/City in Bali with fiscal year 2009-2013. The sampling method used is purposive sampling which took three public service budgets Regency/City in Bali. The analysis technique used is the panel data regression. Based on the analysis can be concluded that SiLPA is the only variable that affect the OPA, while the PAD and Flypaper Effect have no affects Keywords: Local Revenue, Surplus of Financing Budget, Flypaper Effect, Opportunistic Behavior of Regency/City Budget Compiler
Keywords: Local Revenue, Surplus of Financing Budget, Flypaper Effect, Opportunistic Behavior of Regency/City Budget Compiler